Factors Associated with Tuberculosis in Deli Serdang, North Sumatera - Fahmi Syahputra; Rudolf S. Parhusip; Jekson Martiar Siahaan (Masters Program in Public Health, 2019)
Background: Tuberculosis (TB) is still a major public health problem in most developing countries and its incidence is rising in many developed countries. This study aimed to examine factors associated with tuberculosis in Deli Serdang, North SumateraSubjects and Method: This was a cross-sectional study conducted in Deli Serdang, North Sumatera. A sample of 190 study subjects was selected for this study comprising of 95 TB patients and 95 non-TB patients. The dependent variable was tuberculosis. The independent variables were sex, education, BCG immunization, smoking, nutritional status, and dwelling density. Data on TB status were taken from medical record. The other variables were measured by questionnaire. The data were analyzed by a multiple logistic regression.Results: The risk of TB decreased with female sex (OR= 0.33; 95% CI= 0.11 to 0.98; p= 0.046). The risk of TB increased with low education (OR= 8.47; 95% CI= 3.01 to 23.80; p<0.001), had no BCG immunization (OR= 8.86; 95% CI= 3.28 to 23.94; p<0.001), smoking (OR 6.69; 95% CI= 2.20 to 20.38; p=0.001), high dwelling density (OR= 10.35; 95% CI= 4.06 to 26.41; p<0.001), and poor nutritional status (OR= 3.44; 95% CI= 0.85 to 14.03; p= 0.085).Conclusion: The risk of TB decreases with female sex, but increases with low education, had no BCG immunization, smoking, high dwelling density, and poor nutritional status.Keywords: Tuberculosis, sex, BCG immunization, dwelling density, nutritional statusCorrespondence: